Accents of added value in construction 4.0 Ethical observations in dealing with digitization and AI - Weber-Lewerenz, Bianca Christina; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
The book wants to do justice to the complexity surrounding the Digital Transformation and AI in the Construction Industry. User practice experiences show how digital change can be shaped sensibly and constructively, what kind of methods and technologies do exist or can be developed, which fields of application can be explored, by keeping an eye on risks and opportunities. The book works out key factors and core competencies at all levels, which are decisive both for sustainably using innovative technologies and for setting the Seal of Quality of the Construction Industry at home and abroad. Target groups: All people interested in Digitization and AI in the Construction Industry, Companies and Education, everyone who teaches, shares knowledge, researches and explores "the human and technology". The Author With the desire for more courage Bianca Weber-Lewerenz, Civil Engineer, wants to increase the awareness by deepening knowledge and to reach a fundamental reorientation of the Construction Industry. Knowledge creates trust, fears create prejudices. Especially from the building trade, where a lot of strength, self-confidence and potential lie, one expects this courage. She has been following the technological development and the culture of values in Construction since becoming the 1st female bricklayer in Baden-Württemberg. She shows ethically aligned ways for a successful, sustainable digital transformation. With the "Excellence initiative for Sustainable, Human-Led AI in Construction" founded in 2020 she brings the Construction Industry into the general debate on a trustworthy, sustainable AI. For her research she cooperates with the INaB at the Faculty of Civil Engineering, RWTH Aachen University.
Introduction -- Evolution of Ethics in the world of Technology: Philosophical origins -- Human and Technology -- Methode and group of participants of the study -- Methodes of AI -- Use Cases - Experience from the user practice -- Building Culture 4.0 - How do we set responsible value accents? -- Signposts in the discourse on value-based digitization and AI -- Ethics strategy for digital transformation in Construction -- Conclusion and outlook.
Keywords: Civil engineering; Construction industry Management.; Civil Engineering; Construction Management; Construction industry -- Data processing; Construction industry -- Management